2012
DOI: 10.1371/journal.pone.0032730
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of the Sural Nerve Using 22-MHz Ultrasound: A New Approach for Evaluation of Diabetic Cutaneous Neuropathy

Abstract: BackgroundThe application of 22-MHz high-frequency ultrasound allows for visualization of the inner part of the sural nerve. The aim of this study was to evaluate the morphological changes of sural nerves in patients with type 2 diabetes mellitus using ultrasound.Materials and MethodsThe thickness/width (T/W) ratio, the cross-sectional area (CSA) of the sural nerves and the maximum thickness (MT) of the nerve fascicles were measured in 100 patients with type 2 diabetes mellitus and 50 healthy volunteers using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 20 publications
6
42
3
4
Order By: Relevance
“…The results were compared between males and females as well as in regard to the side of the lower limb. We found that the average CSA of the sural nerve (0.14 cm 2 ) was similar to the results obtained by Belsack et al [1] -0.15 cm 2 and Liu et al [8] -0.168 cm 2 . However, our results significantly differed from those obtained by Pazzaglia et al [13] -0.34 cm 2 .…”
Section: Cadaveric -Asiansupporting
confidence: 91%
See 2 more Smart Citations
“…The results were compared between males and females as well as in regard to the side of the lower limb. We found that the average CSA of the sural nerve (0.14 cm 2 ) was similar to the results obtained by Belsack et al [1] -0.15 cm 2 and Liu et al [8] -0.168 cm 2 . However, our results significantly differed from those obtained by Pazzaglia et al [13] -0.34 cm 2 .…”
Section: Cadaveric -Asiansupporting
confidence: 91%
“…The number of examined cadavers was fairly small (n = 37). However, when compared with literature data, our findings are similar to the results obtained on larger groups [1,8]. The mean age of the cadavers was 60 years.…”
Section: Cadaveric -Asiansupporting
confidence: 91%
See 1 more Smart Citation
“…Liu et al (23) found a significantly increased CSA and T/W ratio in the sural nerve in people with diabetes with neuropathy compared with people with diabetes without neuropathy and with healthy control subjects. The CSA of the median nerve in the carpal tunnel of patients with DPN was greater than without DPN and healthy control subjects (24).…”
Section: Discussionmentioning
confidence: 98%
“…To correlate our results with in vivo studies we reviewed ultrasound and MRI data from sciatic and sural nerves in healthy controls (Table 3). 9,16,23,26,42,44 These studies also demonstrate a large variability with regard to CSA, especially of the sural nerve. 9,15,16,26,44 Specifically, the sural nerve CSA as measured by ultrasound ranged from 1.44 to 5.3 mm 2 .…”
Section: Discussionmentioning
confidence: 64%